Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Dalbulus maidis and Peregrinus maidis, both phloem feeding hoppers, induce different volatile profiles in maize. Consequences for a natural enemy - Jorge G. Hill; Eduardo G. Virla; Patricia C. Fernandez; Erica Luft-Albarracin; María V. Coll-Aráoz (Journal of Pest Science, 2024)

Climatological variations of moisture sources for precipitation of North Atlantic tropical cyclones linked to their tracks - Albenis Pérez-Alarcón; Patricia Coll-Hidalgo; José C. Fernández-Alvarez; Ricardo M. Trigo; Raquel Nieto; Luis Gimeno (Atmospheric Research, 2023)

Global Increase of the Intensity of Tropical Cyclones under Global Warming Based on their Maximum Potential Intensity and CMIP6 Models - Albenis Pérez-Alarcón; José C. Fernández-Alvarez; Patricia Coll-Hidalgo (Environmental Processes, 2023)
Future changes in the intensity of tropical cyclones (TCs) under global warming are uncertain, although several studies have projected an upward trend in TC intensity. In this study, we examined the changes in the strength of TCs in the twenty-first century based on the Hurricane Maximum Potential Intensity (HuMPI) model forced with the sea surface temperature (SST) from the bias-corrected CMIP6 dataset. We first investigated the relationship between the mean lifetime maximum intensity (LMI) of major hurricanes (MHs) and the maximum potential intensity (MPI) using the SST from the Daily Optimum Interpolation SST database. The LMI of MHs and the MPI in the last two decades was, on average, 2–3% higher than mean values in the sub-period 1982–2000, suggesting a relationship between changes in MPI and LMI. From our findings, the projected changes in TC intensity in the near-future period (2016–2040) will be almost similar for SSP2-4.5 and SSP5-8.5 climate scenarios. However, TCs will be 9.5% and 17% more intense by the end (2071–2100) of the twenty-first century under both climate scenarios, respectively, compared with the mean intensity over the historical period (1985–2014). In addition, the MPI response to a warmed sea surface temperature per degree of warming is a 5–7% increase in maximum potential wind speed. These results should be interpreted as a projection of changes in TC intensity under global warming since the HuMPI formulation does not include environmental factors (i.e., vertical wind shear, mid-level moisture content and environmental stratification) that influence TC long-term intensity variations. Highlights The maximum potential intensity (MPI) of tropical cyclones is a predictor of their climatological intensities. Tropical cyclones will be 17% more intense than today by the end of the 21 st Century. The maximum potential wind speed will increase by 5–7%/ºC under global warming.

Differential effect of fisheries to the COVID-19 pandemic in the region of Andalusia (Spain) - Marta Cousido-Rocha; Marta González Carballo; Maria Grazia Pennino; Marta Coll; José C. Báez (Marine Policy, 2023)

Chemical Ecology of the host searching behavior in an Egg Parasitoid: are Common Chemical Cues exploited to locate hosts in Taxonomically Distant Plant Species? - C MANZANO; PC FERNANDEZ; JG HILL; E LUFT ALBARRACIN; EG VIRLA; MV COLL ARÁOZ (Journal of Chemical Ecology, 2022)

Human and animal subsistence in northern Iberia during the Late Chalcolithic-Bronze Age: biomolecular insights from Muela de Borja, Ebro Valley - Laura C. Viñas-Caron; Isidro Aguilera; Tina Jakob; Joe W. Walser; Luke Spindler; Maria Fontanals-Coll; Michelle Alexander (Archaeological and Anthropological Sciences, 2022)

Editorial: Managing for the Future: Challenges and Approaches for Disentangling the Relative Roles of Environmental Change and Fishing in Marine Ecosystems - Alida Bundy; Paul E. Renaud; Marta Coll; Stefan Koenigstein; Susa Niiranen; Maria Grazia Pennino; Jamie C. Tam; Morgane Travers-Trolet (Frontiers in Marine Science, 2021)

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams - Magdalena Nagler; Nadine Praeg; Georg H. Niedrist; Katrin Attermeyer; Núria Catalán; Francesca Pilotto; Catherine Gutmann Roberts; Christoph Bors; Stefano Fenoglio; Miriam Colls; Sophie Cauvy‐Fraunié; Brian Doyle; et al. (Journal of Biogeography, 2021)
Aim Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon Methanogenic archaea and methane‐oxidizing microorganisms. Methods To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae , Methanosarcinaceae and Methanobacteriaceae , but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae , Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

Modern Maize Hybrids Have Lost Volatile Bottom-Up and Top-Down Control of Dalbulus maidis, a Specialist Herbivore - María Victoria Coll-Aráoz; Jorge G. Hill; Erica Luft-Albarracin; Eduardo G. Virla; Patricia C. Fernandez (Journal of Chemical Ecology, 2020)

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

Advances and challenges in modelling the impacts of invasive alien species on aquatic ecosystems - X. Corrales; S. Katsanevakis; M. Coll; J. J. Heymans; C. Piroddi; E. Ofir; G. Gal (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Brassinosteroids promote growth, fruit quality and protection against Botrytis on Fragaria x ananassa - R. N. Furio; S. M. Salazar; G. M. Martínez-Zamora; Y. Coll; V. Hael-Conrad; J. C. Díaz-Ricci (European Journal of Plant Pathology, 2019)

Lynx eats cat: disease risk assessment during an Iberian lynx intraguild predation - F. Nájera; S. Sánchez-Cuerda; G. López; T. Del Rey-Wamba; C. Rueda; N. Vallverdú-Coll; J. Panadero; M. J. Palacios; J. V. López-Bao; J. Jiménez (European Journal of Wildlife Research, 2019)

Effect of natural and synthetic Brassinosteroids on strawberry immune response against Colletotrichum acutatum - R. N. Furio; P. L. Albornoz; Y. Coll; G. M. Martínez Zamora; S. M. Salazar; G. G. Martos; J. C. Díaz Ricci (European Journal of Plant Pathology, 2019)

Photo‐identification as a tool to study small‐spotted catshark Scyliorhinus canicula - J. Navarro; A. Perezgrueso; C. Barría; M. Coll (Journal of Fish Biology, 2018)
Photo‐identification (photo‐ID) was tested as a means to identify individual small‐spotted catsharks Scyliorhinus canicula . The spotting pattern of the caudal region of S. canicula was used for the tests and revealed that photo‐ID is an efficient method to identify individuals. Photo‐ID is logistically simple, making it a potential alternative to traditional tagging to provide information on the distribution patterns and population dynamics of S. canicula and related species.

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

Homogenization and analysis of an expanded long‐term monthly rainfall network for the Island of Ireland (1850–2010) - S. Noone; C. Murphy; J. Coll; T. Matthews; D. Mullan; R. L. Wilby; S. Walsh (International Journal of Climatology, 2016)
Long‐term precipitation series are critical for understanding emerging changes to the hydrological cycle. To this end we construct a homogenized Island of Ireland Precipitation ( IIP ) network comprising 25 stations and a composite series covering the period 1850–2010, providing the second‐longest regional precipitation archive in the British‐Irish Isles. We expand the existing catalogue of long‐term precipitation records for the island by recovering archived data for an additional eight stations. Following bridging and updating of stations HOMogenisation softwarE in R ( HOMER ) homogenization software is used to detect breaks using pairwise and joint detection. A total of 25 breakpoints are detected across 14 stations, and the majority (20) are corroborated by metadata. Assessment of variability and change in homogenized and extended precipitation records reveal positive (winter) and negative (summer) trends. Trends in records covering the typical period of digitization (1941 onwards) are not always representative of longer records. Furthermore, trends in post‐homogenization series change magnitude and even direction at some stations. While cautionary flags are raised for some series, confidence in the derived network is high given attention paid to metadata, coherence of behaviour across the network and consistency of findings with other long‐term climatic series such as England and Wales precipitation. As far as we are aware, this work represents the first application of HOMER to a long‐term precipitation network and bodes well for use in other regions. It is expected that the homogenized IIP network will find wider utility in benchmarking and supporting climate services across the Island of Ireland, a sentinel location in the North Atlantic.

Both Volatiles and Cuticular Plant Compounds Determine Oviposition of the Willow Sawfly Nematus oligospilus on Leaves of Salix spp. (Salicaceae) - Celina L. Braccini; Andrea S. Vega; M. Victoria Coll Aráoz; Peter E. Teal; Teresa Cerrillo; Jorge A. Zavala; Patricia C. Fernandez (Journal of Chemical Ecology, 2015)

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Semiochemical and natural product-based approaches to control Spodoptera spp. (Lepidoptera: Noctuidae) - A. Guerrero; Edi A. Malo; J. Coll; C. Quero (Journal of Pest Science, 2014)

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR - L. Selva; P. Ciruela; C. Esteva; M. F. Sevilla; G. Codina; S. Hernandez; F. Moraga; J. J. García-García; A. Planes; F. Coll; I. Jordan; N. Cardeñosa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Valuing acorn dispersal and resprouting capacity ecological functions to ensure Mediterranean forest resilience after fire - C. Puerta-Piñero; L. Brotons; L. Coll; J. R. González-Olabarría (European Journal of Forest Research, 2012)

A simple equation for determining sea surface emissivity in the 3–15 µ m region - R. Niclòs; V. Caselles; E. Valor; C. Coll; J. M. Sánchez (International Journal of Remote Sensing, 2009)

Evaluation of the B ‐method for determining actual evapotranspiration in a boreal forest from MODIS data - J. M. Sánchez; V. Caselles; R. Niclós; E. Valor; C. Coll; T. Laurila (International Journal of Remote Sensing, 2007)

Medical speciality and pattern of medicines prescription - A. Vallano; E. Montan; J. M. Arnau; X. Vidal; C. Pallars; M. Coll; J. R. Laporte (European Journal of Clinical Pharmacology, 2004)

Effect of Spirostane Analogues of Brassinosteroids on Callus Formation and Plant Regeneration in Lettuce (Lactuca sativa) - M. Núñez; W.J. Siqueira; M. Hernández; M.A.T. Zullo; C. Robaina; F. Coll (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Fluid Motion Effect on Metal Toxicity in Bufo arenarum Embryos - J. Herkovits; L. Corró; C. Pérez-Coll; O. Domínguez (Bulletin of Environmental Contamination and Toxicology, 2002)

Effects of Soft Corals on Scleractinian Coral Recruitment. II: Allelopathy, Spat Survivorship and Reef Community Structure - Mauro Maida; Paul W. Sammarco; John C. Coll (Marine Ecology, 2001)
Two field experiments were performed on the Great Barrier Reef, Australia, at Orpheus Island and Lizard Island, respectively, to investigate the effects of allelopathic soft corals on survivorship and community structure of scleractinian coral spat. Ceramic tiles were placed around the allelopathic soft corals Sinularia flexibilis (Quoy & Gaimard 1833) and Sarcophyton glaucum (Quoy & Gaimard 1833), and controls. One control consisted of settlement plates surrounding a scleractinian coral (non‐allelopathic planktivore); another control had no adult soft or scleractinian coral present. The experimental soft corals affected the recruitment of various taxonomic groups of coral spat differentially, as evidenced by the diversity of coral spat settling in treatments and controls. At Orpheus Island (O.I., n = 1038 spat) and Lizard Island (L.I., n = 7032 spat), there were significant differences between recruitment success of the two dominant coral taxa, Pocilloporidae (O.I., 61.4 %; L.I., 20.5 %) and Acroporidae (O.I., 33.7 %; L.I., 53 %). Settlement plates exposed to Sinularia flexibilis at either site had the lowest proportion of acroporid recruits. Diversity indices (Shannon‐Wiener Indices) varied significantly between treatments at both Orpheus and Lizard Islands. This appears to be due to selective inhibition of acroporid spat by Sinularia flexibilis at both sites. Growth of coral spat was higher on settlement plates in the presence of Sarcophyton at Lizard Island. Settlement of most associated epibiota was generally inhibited under these conditions. Coral spat survivorship was highest in the presence of Sinularia at Orpheus Island; at Lizard Island, this was the case with the Sarcophyton treatment. Higher survivorship, and in some cases growth, of coral spat near soft corals was apparently due to reduced competition for space between spat and associated epibiota. This hypothesis is supported by the results of a sister experiment where a coating of Sinularia flexibilis extract on settlement tiles significantly decreased fouling by sessile epibiota. Soft corals have an allelopathic effect on recruitment and early development of scleractinian corals and, consequently, on early coral reef community succession.

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

In situ measurements of skeletal muscle power output using new capacitive strain gauge - P. G. Cooper; G. J. Wilson; D. T. A. Hardman; O. Kawaguchi; Y. -F. Huang; A. Martinez-Coll; R. Carrington; E. Puchert; R. Crameri; C. Horam; S. N. Hunyor (Medical & Biological Engineering & Computing, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of elevated CO 2 and O 3 on the rate and duration of grain growth and harvest index in spring wheat (Triticum aestivum L.) - B. J. MULHOLLAND; J. CRAIGON; C. R. BLACK; J. J. COLLS; J. ATHERTON; G. LANDON (Global Change Biology, 1998)
Wheat ( Triticum aestivum L.) cv. Minaret was grown in open‐top chambers (OTCs) in 1995 and 1996 under three carbon dioxide (CO 2 ) and two ozone (O 3 ) levels. Plants were harvested regularly between anthesis and maturity to examine the rate of grain growth (dG/dt; mg d –1 ) and the rate of increase in harvest index (dHI/dt;% d –1 ). The duration of grain filling was not affected by elevated CO 2 or O 3 , but was 12 days shorter in 1995, when the daily mean temperature was over 3 °C higher than in 1996. Season‐long exposure to elevated CO 2 (680 μmol mol –1 ) significantly increased the rate of grain growth in both years and mean grain weight at maturity (MGW) was up to 11% higher than in the chambered ambient air control (chAA; 383 μmol mol –1 ). However, the increase in final yield obtained under elevated CO 2 relative to the chAA control in 1996 resulted primarily from a 27% increase in grain number per unit ground area. dG/dt was significantly reduced by elevated O 3 under ambient CO 2 conditions in 1995, but final grain yield was not affected because of a concurrent increase in grain number. Neither dG/dt nor dHI/dt were affected by the higher mean O 3 concentrations applied in 1996 (77 vs. 66 nmol mol –1 ); the differing effects of O 3 on grain growth in 1995 and 1996 observed in both the ambient and elevated CO 2 treatments may reflect the contrasting temperature environments experienced. Grain yield was nevetheless reduced under elevated O 3 in 1996, primarily because of a substantial decrease in grain number. The data obtained show that, although exposure to elevated CO 2 and O 3 individually or in combination may affect both dG/dt and dHI/dt, the presence of elevated CO 2 does not protect against substantial O 3 ‐induced yield losses resulting from its direct deleterious impact on reproductive processes. The implications of these results for food production under future climatic conditions are considered.

Growth, light interception and yield responses of spring wheat ( Triticum aestivum L.) grown under elevated CO 2 and O 3 in open‐top chambers - B. J. Mulholland; J. Craigon; C. R. Black; J. J. Colls; J. Atherton; G. Landon (Global Change Biology, 1998)
Spring wheat cv. Minaret was grown to maturity under three carbon dioxide (CO 2 ) and two ozone (O 3 ) concentrations in open‐top chambers (OTC). Green leaf area index (LAI) was increased by elevated CO 2 under ambient O 3 conditions as a direct result of increases in tillering, rather than individual leaf areas. Yellow LAI was also greater in the 550 and 680 μmol mol –1 CO 2 treatments than in the chambered ambient control; individual leaves on the main shoot senesced more rapidly under 550 μmol mol –1 CO 2 , but senescence was delayed at 680 μmol mol –1 CO 2 . Fractional light interception ( f ) during the vegetative period was up to 26% greater under 680 μmol mol –1 CO 2 than in the control treatment, but seasonal accumulated intercepted radiation was only increased by 8%. As a result of greater carbon assimilation during canopy development, plants grown under elevated CO 2 were taller at anthesis and stem and ear biomass were 27 and 16% greater than in control plants. At maturity, yield was 30% greater in the 680 μmol mol –1 CO 2 treatment, due to a combination of increases in the number of ears per m –2 , grain number per ear and individual grain weight (IGW). Exposure to a seasonal mean (7 h d –1 ) of 84 nmol mol –1 O 3 under ambient CO 2 decreased green LAI and increased yellow LAI, thereby reducing both f and accumulated intercepted radiation by ≈ 16%. Individual leaves senesced completely 7–28 days earlier than in control plants. At anthesis, the plants were shorter than controls and exhibited reductions in stem and ear biomass of 15 and 23%. Grain yield at maturity was decreased by 30% due to a combination of reductions in ear number m –2 , the numbers of grains per spikelet and per ear and IGW. The presence of elevated CO 2 reduced the rate of O 3 ‐induced leaf senescence and resulted in the maintenance of a higher green LAI during vegetative growth under ambient CO 2 conditions. Grain yields at maturity were nevertheless lower than those obtained in the corresponding elevated CO 2 treatments in the absence of elevated O 3 . Thus, although the presence of elevated CO 2 reduced the damaging impact of ozone on radiation interception and vegetative growth, substantial yield losses were nevertheless induced. These data suggest that spring wheat may be susceptible to O 3 ‐induced injury during anthesis irrespective of the atmospheric CO 2 concentration. Possible deleterious mechanisms operating through effects on pollen viability, seed set and the duration of grain filling are discussed.

Sequential G-banding FISH on human sperm chromosomes - P. Colls; C. Templado; O. Martinez-Pasarell; F. Darroudi; A. T. Natarajan (Chromosome Research, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Chromosome segregation in a man heterozygous for a pericentric inversion, inv(9)(p11q13), analyzed by using sperm karyotyping and two-color fluorescence in situ hybridization on sperm nuclei - P. Colls; J. Blanco; O. Martínez-Pasarell; F. Vidal; J. Egozcue; C. Márquez; M. Guitart; C. Templado (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)